2007
DOI: 10.1039/b708186c
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolate bridged Cu(ii)–Cu(ii) and Cu(ii)–Zn(ii) complexes of a terpyridinophane azamacrocycle: a solution and solid state study

Abstract: The dinuclear Cu2+ and Zn2+ as well as the mixed Cu2+-Zn2+ complexes of a 5,5''-pentaazaterpyridinophane ligand (L) are able to incorporate imidazolate (Im-) as a bridging ligand. The crystal structure of [Cu(2)L(Im)(Br)(H2O)](CF(3)SO(3))(2).3H2O (1) shows one copper coordinated by the three pyridine nitrogens of the terpyridine unit, one nitrogen of the imidazolate bridge (Im-) and one bromide anion occupying the axial position of a distorted square pyramid. The second copper atom is coordinated by the remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 72 publications
4
26
0
Order By: Relevance
“…The distance is shorter than the one in Cu 2 Zn 2 -SOD (Cu⋅⋅⋅Zn = 6.3 Å) but is close to those in other reported model complexes [9,10,12]. Both Cu(II) atoms are five -coordinated by four nitrogen atoms from L ligand and one nitrogen atom from imidazolate bridge, and all the bond lengths and bond angles are in the normal range [9][10][11][12]. Notably, the coordination geometry around Cu1 is a distorted trigonal-bipyramid as indicated by an index τ value of 0.81, while that of Cu2 is a distorted square-pyramid since the τ value is 0.46 [17].…”
supporting
confidence: 59%
See 2 more Smart Citations
“…The distance is shorter than the one in Cu 2 Zn 2 -SOD (Cu⋅⋅⋅Zn = 6.3 Å) but is close to those in other reported model complexes [9,10,12]. Both Cu(II) atoms are five -coordinated by four nitrogen atoms from L ligand and one nitrogen atom from imidazolate bridge, and all the bond lengths and bond angles are in the normal range [9][10][11][12]. Notably, the coordination geometry around Cu1 is a distorted trigonal-bipyramid as indicated by an index τ value of 0.81, while that of Cu2 is a distorted square-pyramid since the τ value is 0.46 [17].…”
supporting
confidence: 59%
“…As an extension of our work, we designed a new macrocyclic ligand with 1H-imidazol-4-yl-pendants, namely 6, 20-bis (1H-imidazol-4-ylmethyl)-3, 6, 9, 17, 20, 23-hexaazatricyclo [24.3.1.1 11,15 ]hentriaconta-1(29), 11, 13, 15(31), 26(30), 27-hexaene (L, Scheme 1). Herein we report a imidazolate-bridged dinuclear Cu (II) complex [Cu 2 (L)(Im)](ClO 4 ) 3 ·H 2 O (1) obtained by reaction of ligand L and imidazole with Cu(ClO 4 ) 2⋅ 6H 2 O [14,15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The SOD activities were evaluated according to the nitro blue tetrazolium (NBT) assay [12,19,20]. The superoxide anions are generated from the riboflavin-methionine reaction and the NBT is utilized to react with the O ÅÀ 2 to generate blue formazan.…”
Section: Sod Activity Determinationmentioning
confidence: 99%
“…Ever since the X-ray crystal structure analysis revealed the existence of imidazolate-bridged copper-zinc heterodinuclear structure in the active center of the bovine erythrocyte Cu 2 Zn 2 -SOD, a number of imidazolate-bridged dinuclear complexes have been synthesized [8][9][10][11][12]. Comparison between [Cu 2 (TMDT) 2 (im)] 3+ (TMDT = 1, 1, 7, 7-tetramethyldiethylenetriamine) and [Cu 2 (bpim)] 3+ (bpim À = 4,5-bis[2-(2-pyridyl)-ethyliminomethyl]imidazolate) revealed that the imidazolate bridge in the former is stable only over a narrow pH range while the one in the latter is quite stable [13,14].…”
Section: Introductionmentioning
confidence: 99%